Garment pattern making and visual syntax: an essential connection for building the project thinking - da Silva, Maria Antonia Romão; Barbosa, Thassiana de Almeida Miotto; Sanches, Maria Celeste (Revista de Ensino em Artes, Moda e Design, 2020)
This paper describes the results achieved through an integrated assignment performed during the 2nd semester of 2019 in the undergraduate course of Fashion Design at the State University of Londrina (UEL, in the Portuguese acronym), whose pedagogical project is grounded on the Project-Based Learning (PjBL) and on an interdisciplinary approach. Conducted with the first-year students, this study intends to analyze the pedagogical efforts performed to promote the development of their ability with the formal syntax in fashion design and the garment pattern making as parts that combine to build the project thinking. In order to do so, we applied a methodological approach based on a collection of imagery boards and the organization of the MODThink model (EMÍDIO, 2018).